1998
DOI: 10.1002/(sici)1097-4644(19980315)68:4<436::aid-jcb4>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of PDI family proteins during differentiation of mouse F9 teratocarcinoma cells

Abstract: We investigated the expression of protein disulfide isomerase family proteins (PDI, ERp61, and ERp72) in mouse F9 teratocarcinoma cells during differentiation induced by treatment with retinoic acid and dibutyryl cAMP. Each member of this family was expressed at a constitutive level in undifferentiated F9 cells. During differentiation of F9 cells to parietal or visceral endodermal cells the protein level of all these enzymes increased, although the extent of this increase in both protein and mRNA levels varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Another example of a protein that we identified that may also have a significant role in α7 nAChR-related nervous system development is protein disulfide-isomerase A3, which is a member of an enzyme family that catalyzes the rearrangement of disulfide bonds in proteins 80. Although we present the first evidence that this enzyme may interact with the disulfide-bind containing α7 nAChR, there are reports in the literature of the function of protein disulfide-isomerases in developmental regulation 8183. These proteins, and others that we have identified, may have developmentally regulated roles for the localization and/or folding α7 nAChR.…”
Section: Discussionmentioning
confidence: 77%
“…Another example of a protein that we identified that may also have a significant role in α7 nAChR-related nervous system development is protein disulfide-isomerase A3, which is a member of an enzyme family that catalyzes the rearrangement of disulfide bonds in proteins 80. Although we present the first evidence that this enzyme may interact with the disulfide-bind containing α7 nAChR, there are reports in the literature of the function of protein disulfide-isomerases in developmental regulation 8183. These proteins, and others that we have identified, may have developmentally regulated roles for the localization and/or folding α7 nAChR.…”
Section: Discussionmentioning
confidence: 77%
“…However, this method may only catch a small fraction of the natural ERp57 substrates, and it should be noted that these results do not mean that these proteins are exclusively substrates for ERp57. For example, laminin β‐1 and γ‐1 have previously been shown to coimmunoprecipitate equally well with ERp57, ERp72, and PDI [96]. Although it is an extremely interesting and powerful technique that has allowed a unique insight into ERp57 function in vivo , there are several potential limitations with the use of the C‐terminal active site cysteine mutants in determining substrate specificity even after excluding possible problems of the mutation altering the specificity of the enzyme.…”
Section: Pdi Substrate Interactions Without Crosslinkersmentioning
confidence: 99%
“…This was also observed in vivo for thyroglobulin and thrombospondin [33]. In addition, ERp72 was shown to co‐precipitate with laminin during differentiation of mouse F9 teratocarcinoma cells [34]. On the other hand, hPDIR protein has three different a domains with the following active site sequences: CSMC, CGHC, CPHC, respectively.…”
Section: Discussionmentioning
confidence: 57%